Using Substrate-Binding Variants of the cAMP-Dependent Protein Kinase to Identify Novel Targets and a Kinase Domain Important for Substrate Interactions in Saccharomyces cerevisiae - Deminoff, Stephen J. (Copyright © 2006 by the Genetics Society of America, 2006)
Protein kinases mediate much of the signal transduction in eukaryotic cells and defects in kinase function are associated with a variety of human diseases. To understand and correct these defects, we will need to identify the physiologically relevant substrates of these enzymes. The work presented here describes a novel approach to this identification process for the cAMP-dependent protein kinase (PKA) in Saccharomyces cerevisiae. This approach takes advantage of two catalytically inactive PKA variants, Tpk1(K336A/H338A) and Tpk1(R324A), that exhibit a stable binding to their substrates. Most protein kinases, including the wild-type PKA, associate with substrates with a relatively low affinity. The binding observed here was specific to substrates and was dependent upon PKA residues known to be important for interactions with peptide substrates. The general utility of this approach was demonstrated by the ability to identify both previously described and novel PKA substrates in S. cerevisiae. Interestingly, the positions of the residues altered in these variants implicated a particular region within the PKA kinase domain, corresponding to subdomain XI, in the binding and/or release of protein substrates. Moreover, the high conservation of the residues altered and, in particular, the invariant nature of the R324 position suggest that this approach might be generally applicable to other protein kinases.